Hygrothermal performance of six insulation systems for internal retrofitting solid masonry walls. (May 2021) - Jensen, Nickolaj Feldt; Bjarløv, Søren Peter; Rode, Carsten; Andersen, Birgitte; Møller, Eva B
The study investigated the hygrothermal performance and risk of fungal growth in a phenolic foam system with a closed cell structure and a diffusion-open and capillary active lime-cork based insulating plaster, for internal retrofitting purposes. The setup comprised two 40-feet (12.2 m) insulated reefer container with controlled indoor climate, reconfigured with 24 holes (1 × 2 m each) containing solid masonry walls with embedded wooden elements on the interior side. Focus was on the conditions in the masonry/insulation interface and embedded wooden elements, and the performance of the two systems were compared to three diffusion-open insulation systems and one diffusion-tight. The effect of exterior hydrophobisation was also investigated. Relative humidity and temperature were measured in several locations in the test walls over 2½ years, and the risk of fungal growth was evaluated by on-site measurements and the VTT mould-growth model. The findings indicate that internally insulated walls with bare brick exterior surfaces performed poorly with high risk of fungal growth. The effect of exterior hydrophobisation was found to vary with the orientation and the installed insulation system, with a generally positive effect on walls facing south-west but limited effect for north-east. Furthermore, the more diffusion-tight insulation systems were found to perform better in combination with exterior hydrophobisation than the highly diffusion-open systems. The lime-cork insulating plaster showed high relative humidity and risk of moisture-induced problems. The on-site fungal tests showed no growth in the masonry/insulation interface inside the two insulation systems, probably due to high initial pH-value.